2004
DOI: 10.1111/j.1523-1755.2004.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

DDR1-deficient mice show localized subepithelial GBM thickening with focal loss of slit diaphragms and proteinuria

Abstract: The loss of cell-matrix communication in DDR1-deficient podocytes appears to result in excess synthesis of basement membrane proteins leading to disturbed anchorage of foot processes and disruption of the slit diaphragm. Our data suggest that the interaction between type IV collagen and DDR1 plays an important role in maintaining the structural integrity of the GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 30 publications
5
65
0
7
Order By: Relevance
“…[1][2][3] However, current evidence does not support a key role for DDR1 in renal development and physiology, in particular because transgenic mice lacking DDR1 present a close to normal renal phenotype in basal conditions. 11,19 In contrast, DDR1 has been established as an important contributor to a broad variety of pathologic processes, especially in cancer and inflammation, by promoting cell migration, invasion, and survival. 9,10,20 -23 In parallel, several in vitro and in vivo studies have shown that DDR1 was involved in crucial mechanisms leading to fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, current evidence does not support a key role for DDR1 in renal development and physiology, in particular because transgenic mice lacking DDR1 present a close to normal renal phenotype in basal conditions. 11,19 In contrast, DDR1 has been established as an important contributor to a broad variety of pathologic processes, especially in cancer and inflammation, by promoting cell migration, invasion, and survival. 9,10,20 -23 In parallel, several in vitro and in vivo studies have shown that DDR1 was involved in crucial mechanisms leading to fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…33 The bulging of the GBM and ballooning of the glomerular tuft are among the most striking pathologies in nephrin Y3F/Y3F mice, and analogous structures have been reported in mice lacking other podocyte proteins essential for binding to actin or the GBM. 29,[40][41][42][43][44] An additional characteristic of nephrin Y3F/Y3F animals is the disorganized patterning of foot processes. Process formation in podocytes shares biologic features of that within neurons, wherein common cytoskeletal elements and signaling proteins are used to generate elaborate cell-based projections.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of DDR1 led to decreased collagen adhesion, migration of vascular smooth muscle cells, and enhanced proliferation of mesangial cells (Curat and Vogel, 2002;Hou et al, 2001). In addition, DDR1 knockout mice develop localized thickening of GBM and proteinuria, suggesting that collagen IV-DDR1 interaction plays an important role for structural integrity and filtration function in the kidney (Gross et al, 2004).…”
Section: Nonintegrin Receptorsmentioning
confidence: 99%